2017
DOI: 10.1051/meca/2017019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of bursting prediction in tube hydroforming of Al 7020-T6

Abstract: In this study, forming limit diagram (FLD) of tubular material (Al 7020-T6) was determined numerically and experimentally. A set of experimental bulge tests were carried out to determine FLD under combined internal pressure and axial feeding. Also, a numerical approach which is based on the acceleration of plastic strain (i.e., the second derivation) was applied to compute the hydroforming strain limit diagram. Based on this method, the localized necking would be started when the acceleration of the max plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The remaining simulation conditions are listed in Table 3. For numerical prediction of the failure, the second derivative of equivalent plastic strain criterion was employed, as Afshar et al [18] successfully used to predict the failure onset of the 7020-T6 aluminum tube in hydroforming process. In this method, it is assumed that failure occurs when the second derivative of the plastic strain reaches its maximu m value.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…The remaining simulation conditions are listed in Table 3. For numerical prediction of the failure, the second derivative of equivalent plastic strain criterion was employed, as Afshar et al [18] successfully used to predict the failure onset of the 7020-T6 aluminum tube in hydroforming process. In this method, it is assumed that failure occurs when the second derivative of the plastic strain reaches its maximu m value.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…The strain non-uniform index and forming limit diagram are good methods to identify the defect free components by simulation [37]. The fracture and necking parameters were analysed numerically and observed that the static pressure was increased which led to shifting the fracture area from P to C type shaped tubes [38], whereas the forming limit diagram was drawn at necking points of bulged tube with experimentation and simulation on AL-7020-T6 material grade [39].…”
Section: Introductionmentioning
confidence: 99%
“…Alzahrani et al [1] analytically modeled a multi-nose symmetric tube in the hydroforming process based on a mechanistic approach. Afshar et al [2] investigated the forming limit diagrams of hydroformed aluminum tubes to predict bursting, and they compared the numerical results with experimental tests. Keigler et al [3] enhanced the formability of aluminum components via warm hydroforming, and they studied the effect of temperature controlling on wall thickness and microstructure before and after the forming process.…”
Section: Introductionmentioning
confidence: 99%